The volatility of Thai rice price - Abdul Hamid, Baharom; Radam, Alias; Habibullah, Muzafar Shah; Mohd Tahir, Hirnissa (2009)
This study was conducted to explore the varying volatility of rice price for Thailand from the period of 1961 to 2008 using monthly data. The paper provides estimates of two GARCH models, namely, GARCH and EGARCH which were used to capture the stochastic variation and asymmetries in the world rice price. The results indicate that EGARCH model gives better estimate of the volatility of thai rice price. Furthermore the EGARCH model was able to describe the asymmetric volatility in the thai price of rice. It was further discovered that the positive shocks (good news) is more dominant than the negative shock (bad news).